Construction of Paecilomyces fumosoroseus protoplast-transforming system by restriction enzyme-mediated integration (REMI) - YANG Xu-fen; YING Sheng-hua; FENG Ming-guang (浙江大学学报. 农业与生命科学版, 2006)
Phosphinothricin resistance gene Bar vectored by prepared plasmid pAN52-1N-Bar was transformed into the protoplasts of the entomopathogenic fungus Paecilomyces fumosoroseus Pfr116 using the method of restriction enzyme-mediated integration (REMI). The protoplast-based transformation resulted in 6-13 mutants per microgram of the plasmid DNA. Subsequently, PCR and Southern Blotting analyses confirmed successful integration of the Bar gene into the genome DNAs of eight mutants randomly taken. The mutants with a single copy of the inserted gene displayed steady resistance to the chemical after three subcultures. The transformation system featured with lower copies, higher efficiency and genetic stable has proven useful for genetic manipulation of the filamentous fungal biocontrol agent.